Bureaucratic Management as an Obstacle to Implementation of Recommendations Resulting from Customer Satisfaction Survey - Al Braiki, Layla Salem Saleh Fadhel (2011)
This paper seeks to discover if bureaucracy in organizations act as a hindrance to implementation of creative ideas and innovation. It does so by a reviewing different literature written on bureaucracy and its affects and by a theoretical framework where bureaucracy is measured by some common variables. Semi-structured and detailed face to face interviews were carried out with 75 employees of different administrative departments of the Support Services Function of the studied company. The data collected was analyzed using SPSS (Software Package for Social Sciences). After the interviews and applying the relevant SPSS (cross tabulation), the most strongly linked variable emerged as the number of managers above the initiator of the idea. The relation is directly proportional to bureaucracy where as the number of managers’ increase, the time taken to implement a new project / change increases. Conclusively, bureaucracy is largely seen as an obstacle to creativity and it is recommended that the work culture should be such which gives rise to lenient policies and thus, encourage creativity. In addition, work should be done towards reducing the gaps of the hierarchy of organizations, especially tall ones. A practical method can be to hold frequent meetings with employees located at the lower levels of the organization chart. It is anyhow realized that sometimes bureaucracy is needed and is inevitable depending on the business, an organization is involved in.